Distribution and ecology of Ostracoda (Crustacea) from troughs in Turkey - (:unkn) unknown (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2013)
Troughs are artificially transformed natural springs, underground waters, or related habitats. Some effects of such transformation are mentioned in a few studies, but there has been no extensive study on species composition and diversity in troughs. To contribute to the knowledge on the ostracods in troughs, we examined ostracod composition and diversity in 105 troughs from 6 provinces (Bolu, Erzincan, Gaziantep, Kahramanmara, Ordu, Van) in Turkey. The troughs were randomly visited between the years 2006 and 2010. A total of 32 ostracod species and a mean number of 2.16 species per trough were found. The most common 4 species (Heterocypris incongruens, Ilyocypris bradyi, Psychrodromus olivaceus, Candona neglecta) occurred in 57, 48, 34, and 26 different troughs, respectively. A UPGMA dendrogram displayed these 4 species in the same clustering group. The first 2 axes of canonical correspondence analysis explained about 69.5% of the variations in the species data set between 15 species and 5 environmental variables. The 2 most important explanatory variables, altitude (P = 0.008, F = 2.389) and redox potential (P = 0.034, F = 2.230), were the 2 most effective factors on species occurrence in these troughs. Ecological tolerance and optimum estimates of cosmopolitan species were generally higher than the mean values. The Shannon Wiener index showed high values for the 4 most common species, supporting the effect of their dominance. Our results suggest that troughs can have relatively high ostracod richness but evenness can be low due to the strong dominance of one or more species.
Keywords: Ostracoda; trough; ecology; diversity; distribution; SPECIES RICHNESS; BOLU; HABITATS; DIATOMS; PH